Scottish Institute of Sport Annual Report 2005/2006 - Donnelly, D. (Annual report Scottish Institute of Sport, 2006)
Winning - the science of being totally prepared Preparing athletes to compete at the highest levels in world sport demands a range of services of the highest quality. The Institute`s work, has delivered such services through teams of experts in the fields of coaching, sports medicine, sports science, strength and conditioning, and performance lifestyle.